Examining the impact of language learning on cognitive aging in older populations - Spannring, Olivia, author; Grim, Frédérique, advisor; Ivie, Kenny, committee member (Colorado State University. Libraries, 2026)
Dementia and its derivatives, namely Alzheimer’s disease, are becoming increasingly prevalent worldwide. There are nearly 10 million new cases of dementia each year (Alzheimer's Disease International, 2026), most of which are in developing nations. Many pharmacological interventions and potentially significant lifestyle factors have been explored, yet the disease remains incurable and non-preventable. As the incidence of dementia rises, bilingualism has simultaneously become more present globally. With this, bilingualism has piqued the interest of neuroscientists and anatomists, producing research investigating the neural changes in bilingual individuals compared to monolinguals. Through a meta-analytical approach, this paper interprets the results of these studies from the perspective of dementia prevention. Furthermore, it explores language learning itself as a potential avenue for healthy cognitive aging. Finally, the researcher conducted a subjective, short-term, French language learning study on English-speaking senior citizens in the Fort Collins community. Promisingly, the study found that participants' memory improved over the language learning program, indicating the cognitive benefits of small language programs for senior communities, specifically in the clinical context of dementia.
Keywords: dementia; language learning; bilingualism; neuroanatomy; cognitive aging; cognitive reserve; critical period hypothesis; language acquisition; treatment of dementia